Effect of Limestone Calcined Clay Cement (LC3) on Properties of Self-Compacting Concrete - Alferjani , Saad; Altaif , Masoud; Sadaga , Abraik (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
Self-Compacting Concrete (SCC) offers clear advantages in constructability and enhanced durability; however, its widespread use is often limited by high cement content and reliance on imported supplementary cementitious materials, particularly in Libya. In this context, Limestone Calcined Clay Cement (LC3) has emerged as a promising alternative for regions with abundant local clay and limestone resources. This study investigates the feasibility of incorporating LC3, produced from locally available materials within the Libyan context, into SCC as a partial replacement of Portland cement at levels of 15%, 30%, and 45%. The experimental results demonstrate that LC3-based SCC satisfies the required acceptance criteria for rheological performance, despite a gradual reduction in flowability with increasing replacement levels. Mechanical testing indicates that a moderate LC3 replacement enhances early-age strength, while higher replacement levels achieve comparable or improved strength at later ages. Tensile-related properties show no adverse effect even at the highest replacement level when compared to the reference mix. Furthermore, the observed reduction in porosity and increase in ultrasonic pulse velocity confirm improved microstructural refinement, which supports the enhancement of mechanical performance. Overall, the results confirm the technical feasibility of using LC3 in self-compacting concrete (SCC) at replacement levels up to 45% with locally sourced materials, achieving performance comparable to or better than the conventional SCC reference.